TRADISI MERARIK DALAM PERSFEKTIF KOMUNIKASI BUDAYA - Wisri, Wisri; Wawan Juandi; Aminul ‘Alimin (Fakultas Dakwah Universitas Ibrahimy, 2025)
Cultural communication is the transmission of a culture by one group of people to another community, whether the delivery takes the form of verbal or non-verbal communication, where communication and culture cannot be separated, because creatures that do not communicate will be isolated, while culture cannot be understood without communication. This research aims to describe cultural communication in the Merarik tradition in Monggas Village, Kopang District, Central Lombok Regency. This research uses qualitative research methods with an ethnographic type of research. The results of this research can be stated that cultural communication in the Merarik tradition in Monggas Village contains social, religious and cultural values in every delivery, because, if the traditions handed down by the ancestors are good and do not deviate from the teachings of the Islamic religion, then This tradition will continue to be preserved as a culture, as is the case with the Merarik tradition in Monggas Village, Kopang District, Central Lombok Regency.